2011
DOI: 10.1590/s1519-69842011000500019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of population structure and reproductive aspects of the genus Stellifer (Oken, 1817) on the abundance of species on the southern Brazilian coast

Abstract: The differences between abundance and the relationship with aspects of population and reproductive Stellifer rastrifer, Stellifer stellifer and Stellifer brasiliensis were analysed. Data were collected monthly trawl directed for capture of seabob shrimp in Armação do Itapocoroy, an important fishing area on the southern Brazilian coast. The chi-square test showed that the population of S. rastrifer presented values of capture significantly higher than others in all evaluated periods. The frequency distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
(39 reference statements)
0
7
0
2
Order By: Relevance
“…Condition factor (K) is another descriptor widely used in studies on reproductive biology of fishes, predicting that individuals with higher K values are in better physiological conditions (Rodrigues-Filho et al, 2011). In our study, C. edentulus of higher K values were recorded immediately before the periods of greatest reproductive activity, indicating that those individuals store reserves to withstand future losses of energy during gonad maturation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Condition factor (K) is another descriptor widely used in studies on reproductive biology of fishes, predicting that individuals with higher K values are in better physiological conditions (Rodrigues-Filho et al, 2011). In our study, C. edentulus of higher K values were recorded immediately before the periods of greatest reproductive activity, indicating that those individuals store reserves to withstand future losses of energy during gonad maturation.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to those descriptors, Dei Tos et al (2002) used the index of reproductive activity (IRA), a method that 820 combines the proportion of reproducing individuals and values of gonadosomatic index to evaluate the reproductive activity for the whole fish assemblage or single populations. Although the IRA has been broadly applied for fresh water fish assemblages (Dias et al, 2005;Bailly et al, 2008;Braga et al, 2008), few studies used this index to describe reproductive activity of marine fish (Souza & Chaves, 2007;Rodrigues-Filho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A similar length distribution for the congener species Stellifer stellifer was found by Almeida and Branco (2002), in Penha, a county in Santa Catarina Satate, located only a few miles from Porto Belo, when in the fall of 1997 64.5% of the sample were represented by individuals shorter than 8 cm. A larger number of sampled juveniles was also found by Rodrigues-Filho et al (2011) in the same area. This can be explained by the low selectivity in bottom trawls used in shrimp fisheries (Coelho et al, 1985(Coelho et al, , 1987Paiva Filho, 1990, 1995), and therefore very subtle variations in the values of Kr for the two species throughout the year, leads us to disregard any significant seasonal variation in the feeding composition, so that these variations would not be a result of food shortages or changes of abiotic factors, but reflect the changing age structure of the population, since it is influenced by the entry of new individuals periodically, whether small or bigger (youth and adults).…”
Section: Discussionmentioning
confidence: 54%
“…These species occur in abundance in the studied area, as discussed by Rodrigues-Filho (2011), where the overlapping of the reproductive period was observed. In this case, the values of relative condition factor indicated that Stellifer brasiliensis more effectively leverages food resources than S. rastrifer.…”
Section: Introductionmentioning
confidence: 59%
“…In A. nuchalis, females matured at larger sizes than males, a pattern found in other auchenpterids (Freitas et al, 2011;Santos et al, 2013) as well as many other tropical fishes (Barbieri et al, 2004;Nunes et al, 2004;Gomiero et al, 2007;Rodrigues-Filho et al, 2011;Prudente et al, 2015). In this case, size differences between males and females at first maturity may be related to reproductive competition, with males investing in early maturation in order to be ready to reproduce as soon as possible, ensuring the perpetuation of their genes.…”
Section: Discussionmentioning
confidence: 71%